2017
DOI: 10.4067/s0718-58392017000400373
|View full text |Cite
|
Sign up to set email alerts
|

Changes in concentration of volatile compounds in response to defoliation of Muscat of Alexandria grapevines grown under a traditional farming system

Abstract: 373Linalool is a monoterpene, which exhibits floral and spicy aromas as well as a variety of pharmacological effects, including antioxidant, anti-inflammatory, and cardiovascular. Wine flavor is highly dependent on the chemical compounds of berries. The objective of this study was to evaluate the concentration of volatile compounds, especially linalool, in grapes (Vitis vinifera L.) 'Muscat of Alexandria' grown under different cluster light exposure. Four defoliation treatments were applied at veraison, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Currently, the interest in elaborating monovarietal, sparkling, and late harvest wines from this variety is increasing due to its interesting aromatic composition and freshness . Muscat grape cultivars are known for the strong aromatic properties that they confer to wines, mainly due to their high presence of terpenes, which present low odor thresholds .…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, the interest in elaborating monovarietal, sparkling, and late harvest wines from this variety is increasing due to its interesting aromatic composition and freshness . Muscat grape cultivars are known for the strong aromatic properties that they confer to wines, mainly due to their high presence of terpenes, which present low odor thresholds .…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
“…152 Currently, the interest in elaborating monovarietal, sparkling, and late harvest wines from this variety is increasing due to its interesting aromatic composition and freshness. 23 Muscat grape cultivars are known for the strong aromatic properties that they confer to wines, mainly due to their high presence of terpenes, which present low odor thresholds. 153 Belancic et al 154 reported that Moscatel de Alejandría and Moscatel Rosada presented similar total free terpenoids with a concentration close to 2100 μg L−1 154 , although Moscatel de Alejandría contained abundant concentrations of total bound terpenols.…”
Section: Moscatel De Alejandríamentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of flavonols in grapes is activated in response to treatments with UV and sunlight (Haselgrove et al, 2000). Light interception at fruit zone is determined by the training system, and its management can increase sunlight exposure improving grape quality (Pascual et al, 2017). In this way, temperature appears to have a less influence on flavonol synthesis, compared to sunlight (Makris et al, 2006;Flamini et al, 2013).…”
Section: Peumentioning
confidence: 99%